Does electrification affect rural poverty and households' non-food spending? Empirical evidence from western Indonesia - Ikhsan Ikhsan; Khairul Amri (Cogent Economics & Finance, 2022)
The study aims to determine the effect of electrification on rural poverty and households' non-food spending (NFS). Using a cross-province dataset of western Indonesia from 2007 through 2017, an econometric model was used to analyze the causal relationship between the variables. The econometric model is a panel cointegration test, panel VECM, and Granger causality tests. The study pointed out three main findings. Firstly, there is a long-run equilibrium relationship between rural poverty and households' NFS and electrification. In the long run, the electrification program has a negative and significant on households' NFS. Secondly, in the short run, electrification significantly reduces poverty and increases households' NFS. Thirdly, the Granger causality test pointed out that there is one-way causality from electrification to rural poverty and households' NFS. The rural poverty reduction and the raising households' NFS are positive impacts of the electrification program. Therefore, the local governments in western Indonesia should be electrification programs as one of the strategic options for rural poverty reduction in the region.
Keywords: 330; electrification; rural poverty; household's non-food spending; panel vector error correction model; Granger causality test